2010
DOI: 10.1080/0972060x.2010.10643877
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Chamomile Cultivars Introduced and Adapted in Egypt

Abstract: The Egyptian chamomile has a good reputation in the export markets due to hand pick of the flower heads and application of organic farming system. However, in the last decade exports of chamomile faced some problems due to inconsistency with the required oil quality. Accordingly, a long term program was initiated for quality improvement of chamomile grown in Egypt. This approach depended on a selection program within the local variety as well as introduction of new sources from other countries to diversify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Chamomile use has a long history in Egypt, and it is still important. Organic farming and handed-picked flower heads give Egyptian chamomile a good reputation in export markets [19]. The total chamomile cultivation area reached approximately 9500 acres and ranked second among the cultivated medicinal plants in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Chamomile use has a long history in Egypt, and it is still important. Organic farming and handed-picked flower heads give Egyptian chamomile a good reputation in export markets [19]. The total chamomile cultivation area reached approximately 9500 acres and ranked second among the cultivated medicinal plants in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Most characteristics of the resulting fruits did not differ significantly between all GA3 and melatonin treatments 30 and so, high productivity of artichoke cultivars could be achieved by using suitable cultivar and cultivation management such as foliar application treatments of GA3 and melatonin 31 . The yield of essential oil of Matricaria recutita depends on the environmental conditions of plant sites as well as the plant genotype 9,10,2,6,12 . The essential oil yields differ with some research which were highly or low and this may be due to many factors e.g., different locations, growing conditions (soil and climate) 32,33 .…”
Section: Essential Oil Content and Its Constituents A Essential Oil Percentagementioning
confidence: 99%
“…The essential oil yields differ with some research which were highly or low and this may be due to many factors e.g., different locations, growing conditions (soil and climate) 32,33 . Some authors have also reported variability of the oil content under the influence of different factors as soil type 33 , day light and irradiance 34 , and time of flower harvest 6,35 . Thus, in our research cutting was performed two times (February and March).…”
Section: Essential Oil Content and Its Constituents A Essential Oil Percentagementioning
confidence: 99%
See 2 more Smart Citations